2013
DOI: 10.1021/jf401477c
|View full text |Cite
|
Sign up to set email alerts
|

Tannin Structural Elucidation and Quantitative 31P NMR Analysis. 1. Model Compounds

Abstract: An unprecedented analytical method that allows simultaneous structural and quantitative characterization of all functional groups present in tannins is reported. In situ labeling of all labile H groups (aliphatic and phenolic hydroxyls and carboxylic acids) with a phosphorus-containing reagent (Cl-TMDP) followed by quantitative 31 P NMR acquisition constitutes a novel fast and reliable analytical tool for the analysis of tannins and proanthocyanidins with significant implications for the fields of food and fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 28 publications
2
78
0
Order By: Relevance
“…The 31 P NMR spectrum (Fig. 3) highlighted the presence of tannins, as reported in Melone et al [26,27], in particular, it was possible to detect an high amount of ellagic acid. In fact, 31 P NMR spectra of ellagic acid derivatized with 2-chloro-4,4,5,5-tetramethyl-1,3,2-dioxaphospholane are dominated by two characteristic peaks at 141.7 ppm and 139.2 ppm [26] with an identical integration, similar to the spectrum reported in Fig.…”
Section: Vasasupporting
confidence: 75%
See 1 more Smart Citation
“…The 31 P NMR spectrum (Fig. 3) highlighted the presence of tannins, as reported in Melone et al [26,27], in particular, it was possible to detect an high amount of ellagic acid. In fact, 31 P NMR spectra of ellagic acid derivatized with 2-chloro-4,4,5,5-tetramethyl-1,3,2-dioxaphospholane are dominated by two characteristic peaks at 141.7 ppm and 139.2 ppm [26] with an identical integration, similar to the spectrum reported in Fig.…”
Section: Vasasupporting
confidence: 75%
“…Extractives, lignin and holocellulose were characterized by nuclear magnetic resonance (2D-HSQC and 31 P) and gel permeation chromatography (GPC). Both these techniques are important tools in lignocellulose characterization [24][25][26][27]. In particular, analytical applications of 31 P NMR have already been reported [28,29] in the study of archaeological unguents and polymer degradation.…”
Section: Introductionmentioning
confidence: 99%
“…As for the GAL, the esterification process reduced the aliphatic hydroxyl content (150 to 145.5 ppm), whereas the addition of GA units increased the phenolic hydroxyl content (144.7 to 136.6 ppm), which was expected. Additionally, the peaks for S-type (around 142.7 ppm), G-type (140.0 to 139.0 ppm), and H-type (139.5 to 137.3 ppm) phenolic hydroxyl groups disappeared and were replaced with ortho-disubstituted (142.0 to 140.4 ppm) and ortho-substituted (140.3 to 137.6 ppm) phenolic hydroxyl groups from GA resource (Melone et al 2013). The grafted GA moieties of GAL increased the phenolic hydroxyl content to 4.43 mmol/g as compared to 2.14 mmol/g for unmodified lignin; the grafting increased the molecular weight (Mw) from 2200 g/mol for the unmodified lignin to 2996 g/mol for the GAL.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…31 P NMR spectra of unmodified lignin and GAL were recorded on a Brüker 500 MHz NMR spectrometer (Brüker BioSpin (Rheinstetten, Germany)) according to the method of Xin et al (2014) using 2-chloro-4,4,5,5-tetramethyl-1,2,3-dioxaphospholane (TMDP) as the phosphitylating reagent.…”
Section: Characterizationmentioning
confidence: 99%
“…A systematic study on validating quantitative 31 P NMR has showed that there is no significant difference between 31 P qNMR and chromatographic methods with respect to analytical capability [46]. Apart from the direct quantitative analysis of common phosphorus containing compounds such as ATP (adenosine-5 0 -triphosphate), ADP (adenosine-5 0 -diphosphate), and AMP (adenosine-5 0 -monophosphate) using 31 P NMR [47], in order to quantify compounds with various types of hydroxyl groups including aliphatic, phenolic, and carboxylic acids, a strategy of making use of derivatizing reaction with these hydroxyl groups to give phosphitylated products and associating with 31 P qNMR has been widely employed [48][49][50]. Inevitably, this strategy will increase economical and time costs.…”
Section: P 1d Qnmrmentioning
confidence: 99%